Technical note: Sustainable snail meal enhances duck egg production and health - Yunqian He; Saikun Pan; Shengjun Wu (Poultry Science)
This study evaluated the effects of replacing soybean meal with snail meal on laying performance, egg quality, and blood parameters in laying ducks. Five experimental diets with graded levels of soybean meal replacement by snail meal were formulated: T0 (0% replacement), T1 (25% replacement), T2 (50% replacement), T3 (75% replacement), and T4 (100% replacement). Ducks fed the T2 (50% replacement) diet showed the highest egg production rate (87%), average egg weight (68.0 g), and egg mass (59.2 g/day), along with the lowest feed conversion ratio (2.18). Egg quality also improved, with increased yolk color score (10.0), Haugh unit (86.0), and eggshell strength (4.1 kg/cm²). Serum analysis revealed higher superoxide dismutase (SOD) (85.48 U/mL), glutathione peroxidase (GPX) (148.59 U/mL), and IgG (2.34 g/L) levels in the 50% group, indicating enhanced antioxidant and immune functions. These findings suggest that replacing 50% of soybean meal with snail meal optimizes laying performance and physiological health in ducks, and offers a promising strategy for sustainable protein substitution in poultry diets.